Derivation of a simple risk calculator for predicting clinical worsening in patients with pulmonary hypertension due to interstitial lung disease - K. El-Kersh; R. Bag; N. Bhatt; C. King; A. Waxman; F. Rischard; H. Kim; D. Cella; E. Shen; SD Nathan (JHLT Open)
Background: Pulmonary hypertension due to interstitial lung disease (ILD-PH) portends very poor clinical outcomes, with a median survival time of 1.5 to 2 years. Currently, there is no tool to assess the risk of clinical worsening in patients with ILD-PH. Our aim was to derive a simple and practical risk calculator that could be used to predict risk of clinical worsening in patients with ILD-PH. Methods: The INCREASE study was a 16-week study that evaluated inhaled treprostinil in patients with ILD-PH. Baseline data from patients who were randomized to the placebo arm (n=163) and thus untreated with any approved pulmonary artery vasodilators were used to derive a risk calculator. The endpoint of interest was the time to clinical worsening. Stepwise regression, Harrell’s c-index, and clinician input were used to derive 2 multivariable Cox PH models from a set of candidate variables. The models were then simplified by applying a point-scoring system to the predictors and refitting with total point score as the covariate. Total point scores were grouped into 3 risk strata (lower, intermediate, and higher). Results: Two versions of a risk calculator were derived. The first was a non-invasive risk calculator which included NT-proBNP and FVC%/DLCO%, and a second adds cardiac index, an invasive parameter, to the above two parameters. For the total point score models, the estimated c-indices were 0.703 (95% CI: 0.635, 0.783) and 0.683 (95% CI: 0.612, 0.761) for the invasive and non-invasive model, respectively. Conclusion: These two risk calculators provide a simple way to risk stratify ILD-PH patients with clinically useful discrimination. The calculators are easy to employ in clinical practice, since they utilize assessments commonly collected in the care of patients with ILD-PH. Moreover, the calculators can provide clinicians with important prognostic information which can be used to reinforce the benefits of therapy. The risk calculators may also find utility as part of the composite allocation score of ILD-PH patients listed for lung transplant. Future research in this area could include incorporating longer-term outcomes as well as validating the risk models in a separate patient population.